Exploratory factor analysis of the Brazilian OHIP for edentulous subjects - SOUZA, R. F.; LELES, C. R.; GUYATT, G. H.; PONTES, C. B.; DELLA VECCHIA, M. P.; NEVES, F. D. (Journal of oral rehabilitation, 2010)
Summary  The use of seven domains for the Oral Health Impact Profile (OHIP)‐EDENT was not supported for its Brazilian version, making data interpretation in clinical settings difficult. Thus, the aim of this study was to assess patients’ responses for the translated OHIP‐EDENT in a group of edentulous subjects and to develop factor scales for application in future studies. Data from 103 conventional and implant‐retained complete denture wearers (36 men, mean age of 69·1 ± 10·3 years) were assessed using the Brazilian version of the OHIP‐EDENT. Oral health‐related quality of life domains were identified by factor analysis using principal component analysis as the extraction method, followed by varimax rotation. Factor analysis identified four factors that accounted for 63% of the 19 items total variance, named masticatory discomfort and disability (four items), psychological discomfort and disability (five items), social disability (five items) and oral pain and discomfort (five items). Four factors/domains of the Brazilian OHIP‐EDENT version represent patient‐important aspects of oral health‐related quality of life.